Learning GeoSpatial analysis with Python : an effective guide to geographic information system and remote sensing analysis using Python 3 - Lawhead, Joel (Packt Publishing, 2015)
An effective guide to geographic information systems and remote sensing analysis using Python 3About This Book Construct applications for GIS development by exploiting Python This focuses on built-in Python modules and libraries compatible with the Python Packaging Index distribution systemno compiling of C libraries necessary This practical, hands-on tutorial teaches you all about Geospatial analysis in Python Who This Book Is ForIf you are a Python developer, researcher, or analyst who wants to perform Geospatial, modeling, and GIS analysis with Python, then this book is for you. Familarity with digital mapping and analysis using Python or another scripting language for automation or crunching data manually is appreciatedWhat You Will Learn Automate Geospatial analysis workflows using Python Code the simplest possible GIS in 60 lines of Python Mold thematic maps with Python tools Get hold of the various forms that geospatial data comes in Produce elevation contours using Python tools Create flood inundation models Apply Geospatial analysis to find out about real-time data tracking and for storm chasingIn DetailGeospatial Analysis is used in almost every field you can think of from medicine, to defense, to farming. This book will guide you gently into this exciting and complex field. It walks you through the building blocks of geospatial analysis and how to apply them to influence decision making using the latest Python software. Learning Geospatial Analysis with Python, 2nd Edition uses the expressive and powerful Python 3 programming language to guide you through geographic information systems, remote sensing, topography, and more, while providing a framework for you to approach geospatial analysis effectively, but on your own terms. We start by giving you a little background on the field, and a survey of the techniques and technology used. We then split the field into its component specialty areas: GIS, remote sensing, elevation data, advanced modeling, and real-time data. This book will teach you everything you need to know about, Geospatial Analysis from using a particular software package or API to using generic algorithms that can be applied. This book focuses on pure Python whenever possible to minimize compiling platform-dependent binaries, so that you don't become bogged down in just getting ready to do analysis. This book will round out your technical library through handy recipes that will give you a good understanding of a field that supplements many a modern day human endeavors. Style and approach This is a practical, hands-on tutorial that teaches you all about Geospatial analysis interactively using Python.
Includes index.
Keywords: Geospatial data.; Python (Computer program language); elektronické knihy; electronic books